Strategi Pengorganisasian Pembelajaran Inklusif untuk Anak Berkebutuhan Khusus di Sekolah Dasar - Isyatul Karimah; Suyatno Suyatno; Sukirman Sukirman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to identify effective strategies for organizing inclusive education for children with special needs in elementary schools. The research employs an exploratory qualitative method, with primary data sources including observation, interviews, and documentation at Sekolah Kreatif Muhammadiyah 2 Bontang, East Kalimantan. The study founds that collaborative and comprehensive strategies, continuous professional development, differentiated instruction approaches, and rigorous control and supervision are key to successful inclusive education implementation. Data analysis reveals that collaboration among teachers, parents, and support staff is crucial to creating an inclusive learning environment that supports the development of children with special needs. This study recommends improving teacher training, as well as active community involvement and support from relevant parties to overcome challenges in inclusive education and achieve more optimal results. Thus, it is expected to improve the quality of inclusive education in Indonesia and provide better opportunities for children with special needs to achieve their potential optimally and sustainably.